2023
DOI: 10.1021/acs.jpclett.2c03674
|View full text |Cite
|
Sign up to set email alerts
|

Single-Photon Emission from Two-Dimensional Materials, to a Brighter Future

Abstract: Single photons, often called flying qubits, have enormous promise to realize scalable quantum technologies ranging from an unhackable communication network to quantum computers. However, finding an ideal single-photon emitter (SPE) is a great challenge. Recently, two-dimensional (2D) materials have shown great potential as hosts for SPEs that are bright and operate under ambient conditions. This Perspective enumerates the metrics required for an SPE source and highlights that 2D materials, because of reduced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Their fabrication in monolayers and few layers is achieved using mostly strain engineering to induce localized defects, and their main characteristics are a large single‐photon purity and low‐temperature operation that only in a few cases reaches 77 K. These single‐photon sources can be easily controlled by applying an external electric field, electrostatic gating, and local strain. [ 146 ]…”
Section: Solid‐state Single‐photon Sources In the Infraredmentioning
confidence: 99%
See 2 more Smart Citations
“…Their fabrication in monolayers and few layers is achieved using mostly strain engineering to induce localized defects, and their main characteristics are a large single‐photon purity and low‐temperature operation that only in a few cases reaches 77 K. These single‐photon sources can be easily controlled by applying an external electric field, electrostatic gating, and local strain. [ 146 ]…”
Section: Solid‐state Single‐photon Sources In the Infraredmentioning
confidence: 99%
“…Their fabrication in monolayers and few layers is achieved using mostly strain engineering to induce localized defects, and their main characteristics are a large single-photon purity and low-temperature operation that only in a few cases reaches 77 K. These single-photon sources can be easily controlled by applying an external electric field, electrostatic gating, and local strain. [146] One of the main limitations of these single-photon sources is that the microscopy origin of the defects responsible for single photons is as yet unclear. [146] Their brightness is also not on par with other 2D materials or color centers in diamond and SiC.…”
Section: D Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain-localized excitons in 2D semiconductors can serve as single photon emitters (SPEs) that are critical to the development of quantum information technologies such as quantum communication, computing, and sensing. While hexagonal boron nitride (hBN) and WSe 2 are two of the most widely studied 2D SPE hosts, interests in exploring SPEs and developing strategies to improve the SPE performance have grown in recent years. Particularly, Luo et al demonstrated deterministic localization of SPEs in multilayer GaSe using nanopillar arrays, and showed that strain plays a critical role in controlling the brightness and emission wavelength of SPEs using nanoscale spatial resolution imaging technique . Nevertheless, significant performance improvement is still needed to satisfy application requirements.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that cavity interactions, , defect engineering, and electrostatic doping , can enhance the performance of SPEs in 2D semiconductors such as hBN and WSe 2 . Notably, electrostatic doping has been considered as an effective and practical approach to effectively enhance the brightness, single photon purity, and operating temperatures of SPEs in monolayer WSe 2 by controlling carrier concentrations, maximizing the radiative recombination of strain-localized neutral excitons, and suppressing the background of defect-bound states.…”
mentioning
confidence: 99%